Study of Improving Cluster Supply Chain Capability at PT. XYZ Through The Implementation of Digital Connectivity - Rahady, Peri; Tricahyono, Dodie; Dudija, Nidya (Indonesian Scientific Publication, 2025)
This study explores how digital connectivity can enhance the operational effectiveness of cluster-based supply chains, using PT XYZ as a case example. In an increasingly volatile and complex market environment, real-time data integration has emerged as a strategic necessity for supply chain agility and responsiveness. The findings reveal that digital connectivity significantly contributes to improving coordination, accelerating decision-making, reducing lead times by up to 30%, and lowering operational costs by approximately 20%. Central to this transformation is the adoption of Enterprise Resource Planning (ERP) systems, which enable predictive analytics, real-time inventory tracking, and scenario-based planning—tools that support both tactical and strategic decision-making. In addition, cloud platforms and collaborative digital tools further streamline communication across supply chain partners. Despite these improvements, the system at PT XYZ remains only partially automated, especially across geographically distributed clusters, pointing to the pressing need for unified digital integration. To address this gap, the study proposes a digital integration framework that emphasizes standardization of systems, infrastructure readiness, and change management strategies. Using a qualitative case study approach, the research draws on interviews, document analysis, and observations to evaluate implementation outcomes and identify key enablers and barriers. The findings offer practical insights for organizations seeking to enhance supply chain performance through digital.